Diagnosis of Resistant Hypertension (Northern International Medical College Journal, 2017)
Hypertension is a major risk factor of cardiovascular death in Bangladesh and worldwide. Resistant hypertension as well as uncontrolled hypertension with 3 or more antihypertensive agents is increasingly common in clinical practice. Clinicians should exclude pseudoresistant hypertension, which results from nonadherence to medications or from elevated blood pressure related to the white coat syndrome. Resistant hypertension may be associated with secondary causes of hypertension including obstructive sleep apnea or primary aldosteronism.Northern International Medical College Journal Vol.8(1) July 2016: 196-198